Basics of microwave filter design introduction to filter basics - Swanson, Daniel G. (IEEE, 2010)
This course will provide an introduction covering the superheterodyne receiver, the ideal brick wall filter, and insertion loss and return loss concepts. Additionally, approximation theory and equal ripple functions as well as amplitude and group delay responses will be discussed. Lowpass prototypes will be covered in this course including Chebyshev and elliptic prototypes. The course will review the process of finding prototype element values, frequency and impedance scaling, and transformations to highpass, bandpass, and bandstop. Finally, unloaded Q and loss will be discussed. In particular, Qu and volume, basic concepts will be reviewed. Additionally, Qu for common technologies and estimating midband loss will be discussed
Description based on online resource; title from title screen (IEEE Xplore Digital Library, viewed November 13, 2020)
Keywords: Receivers; Film